Equilíbrio corporal à posturografia estática na migrânea vestibular - Gorski, Leslie Palma [UNIFESP] (2017)
PURPOSE: to evaluate the body balance of patients with vestibular migraine on static posturography. METHOD: An experimental group of 31 patients with medical diagnosis of vestibular migraine in the intercritical period of the condition and a control group of 31 healthy individuals matched for age and sex were submitted to Tetrax Interactive Balance System (Tetrax IBS) Postography in eight sensory conditions. The parameters analyzed were: stability index - measures the amount of oscillation, overall stability and ability to compensate for postural modifications; Weight distribution index - compares deviations in weight distribution; Synchronization index - measures the symmetry in the weight distribution; Postural oscillation frequency - indicates the frequency range with more oscillation; and Fall risk index - expresses the likelihood of falls. RESULTS: The stability index was higher in the experimental group in all eight conditions, with a significant difference between the groups in six of them. The weight distribution index was higher in the experimental group in all conditions, with a significant difference in three of them. The postural oscillation values were higher in the experimental group in all frequency ranges in the eight sensory conditions with a significant difference in F1 in one condition, in F2-F4 in six, in F5-F6 in five, and in F7-F8 in two. The number of cases with preferential oscillation in F2-F4 was significantly higher in the experimental group in three conditions and in F5-F6 in two. The falling risk in the experimental group was significantly higher than the control group. CONCLUSION: Patients with vestibular migraine present in static posturography impairment of body balance.